The Effect of Nutrition Counseling Intervention on Attitudes About Nutrition in SSB Kancil Mas Athletes - Cindy Feriska Saputri; Linda Riski Sefrina; Millyantri Elvandari (Sport and Nutrition Journal, 2025)
Soccer is the most popular sport in the world. In Indonesia, this sport has a high enthusiasm. The importance of providing nutrition education through nutrition counseling can directly impact the health and performance of athletes. If knowledge and attitudes towards nutrition are inadequate and understanding the nutritional role of various types of food is not appropriate, this can cause health and fitness problems. This study aimed to determine the effect of providing nutritional counseling on attitudes about nutrition in SSB Kancil Mas athletes. This research is experimental with a one-group pre- and post-test design conducted at SSB Kancil Mas Karawang. Respondents of this study amounted to 15 people. The respondents in this study were selected using a purposive random sampling technique, and data analysis was conducted using the Wilcoxon Test. The results showed a significant difference in attitude values before and after providing nutritional counseling (p<0.05). Providing nutritional counseling improves attitudes about nutrition in SSB Kancil Mas Karawang athletes.